2007
DOI: 10.2478/v10006-007-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Hermite Spline Interpolation on Patches for Parallelly Solving the Vlasov-Poisson Equation

Abstract: This work is devoted to the numerical simulation of the Vlasov equation using a phase space grid. In contrast to ParticleIn-Cell (PIC) methods, which are known to be noisy, we propose a semi-Lagrangian-type method to discretize the Vlasov equation in the two-dimensional phase space. As this kind of method requires a huge computational effort, one has to carry out the simulations on parallel machines. For this purpose, we present a method using patches decomposing the phase domain, each patch being devoted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…If we treat them separately on different processors, we have to take care of interface conditions. A parallelization procedure of the semi-Lagrangian method is presented in [13]. (3) The Back-Trajectory method becomes particularly interesting when we use the geostationary approximation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If we treat them separately on different processors, we have to take care of interface conditions. A parallelization procedure of the semi-Lagrangian method is presented in [13]. (3) The Back-Trajectory method becomes particularly interesting when we use the geostationary approximation.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the case of periodic boundary conditions (see [13]), the values of the function outside [x 0 , x N ] can not be known. Therefore we have to use the values of f at time t n inside this interval to compute the distribution function at time t n + Δt.…”
Section: Thus the Hermite Boundary Conditions Implymentioning
confidence: 99%
See 2 more Smart Citations
“…Vlasov simulations based on the semi-Lagrangian approach by using the cubic spline interpolation operator have been carried out by Cheng and Knorr [1976] and by Crouseilles et al [2007, 2009, andreferences therein]. Crouseilles et al [2007Crouseilles et al [ , 2009 also showed how to use the cubic spline to determine the derivatives of a tabulate function with equal mesh size for a given Hermite boundary conditions. In Appendix B, we demonstrate that we can use the cubic spline to determine the derivatives of a non-equal-spacing tabulated function with either periodic or nonperiodic boundary conditions.…”
Section: A2 Spatial Derivative Solvermentioning
confidence: 99%